2022
DOI: 10.1177/17588359221086916
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatment strategies for metastatic triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous subtype of breast cancer that is often associated with an aggressive phenotype and a poor prognosis. Cytotoxic chemotherapy remains the mainstay of treatment for most patients with metastatic TNBC (mTNBC), but duration of response is often short and median overall survival is only 12–18 months. Therefore, it is critical to identify novel treatment strategies to improve outcomes for these patients. In this review article, we discuss recent advances in trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 110 publications
(120 reference statements)
0
10
0
Order By: Relevance
“…Combining ICIs with chemotherapy has had more promising activity. Pembrolizumab in combination with chemotherapy has been approved as a first-line treatment for PD-L1+ advanced TNBC [ 6 , 7 , 8 , 9 , 10 ]. ICIs are also being combined with PARP inhibitors and antibody–drug conjugates (ADCs) for evaluation in clinical studies [ 2 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combining ICIs with chemotherapy has had more promising activity. Pembrolizumab in combination with chemotherapy has been approved as a first-line treatment for PD-L1+ advanced TNBC [ 6 , 7 , 8 , 9 , 10 ]. ICIs are also being combined with PARP inhibitors and antibody–drug conjugates (ADCs) for evaluation in clinical studies [ 2 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC), characterized by the lack of expression of the estrogen receptor (ER), progesterone receptor (PgR), and human epidermal growth factor receptor 2 (HER2), accounts for approximately 12-15% of breast cancers diagnosed worldwide (1)(2)(3). Despite extensive studies that have led to a better understanding of its clinical and biological heterogeneity (4)(5)(6), TNBC remains the most aggressive breast cancer subtype, owing to its high visceral metastatic potential, especially to the lungs and brain (7): The median overall survival (OS) is 10-13 months in the metastatic setting (1).…”
Section: Introductionmentioning
confidence: 99%
“…As reported in the GLOBOCAN 2020 survey, the number of breast cancer (BC) has recently overtaken lung cancer as the most common cancer type worldwide and has become the leading cause of cancer death in women ( 1 ). It has been reported that triple negative breast cancer (TNBC) makes up approximately 15%-20% of all BC patients, which is characterized by estrogen (ER), progesterone (PR), and human epidermal growth factor receptor-2 (HER2) negativity ( 2 ). Due to the variety and heterogeneity, distinct molecular subtypes of TNBC are still not completely understood.…”
Section: Introductionmentioning
confidence: 99%